AIE-active tetraphenylethene functionalized metal–organic framework for selective detection of nitroaromatic explosives and organic photocatalysis. Issue 75 (30th August 2016) - Li, Qiu-Yan; Ma, Zheng; Zhang, Wen-Qiang; Xu, Jia-Long; Wei, Wei; Lu, Han; Zhao, Xinsheng; Wang, Xiao-Jun
Abstract : A luminescent MOF containing an AIE-active TPE moiety works as a selective sensor for detecting nitroaromatic explosives, as well as an efficient heterogeneous photocatalyst for CDC reactions mediated by visible light. Abstract : AIE-active luminogen tetraphenylethene (TPE) was incorporated into a UiO-isoreticular zirconium metal–organic framework via the strategy of mixed dicarboxylate struts, and the resulting functionalized MOF shows a strong blue-green emission and selective sensing of nitroaromatic explosives 2, 4, 6-trinitrophenol (TNP) and 2, 4-dinitrophenol (DNP) through fluorescence quenching. Moreover, the luminescent MOF exhibits efficient photocatalytic activity for aerobic cross-dehydrogenative coupling reactions mediated by visible light.